Assessment of quality of presentation of clinical trial results in Russia in accordance with CONSORT standards - A. R. Kasimova; N. M. Guseinova (Реальная клиническая практика: данные и доказательства)
The gold standard for presenting evidence of the effectiveness and safety of medical procedures is randomized controlled trials (RCTs). For the research results to be available to other specialists and have potential weight in the scientific community, they must be described and published in accordance with generally accepted international standards, CONSORT, or Consolidated standards of reporting trials.Objective: to analyze the quality of presenting the results of clinical trials in the Russian Federation in accordance with CONSORT standards.Materials and methods. The following Russian journals were selected for the study: "Scientific and Practical Rheumatology", "Good Clinical Practice", "Social and Clinical Psychiatry", "S. S. Korsakov Journal of Neurology and Psychiatry". The selection of target journals was based on two main indicators of the journal rating in the Russian Science Citation Index; according to the SCIENCE INDEX rating and the rating of psychiatric journals by the impact factor RSCI 2016. Journals in the fields of biomedicine (Scientific and Practical Rheumatology), clinical pharmacology (Good Clinical Practice), and journals in the fields of psychology and psychiatry (Social and Clinical Psychiatry, S. S. Korsakov Journal of Neurology and Psychiatry) were selected. Each article was assessed according to the CONSORT checklist items, and the presence or absence of data on the presented items was noted. When studying the articles, the presence or absence of a flowchart in the article was also analyzed, which significantly improves the quality of the written article and compliance with international standards for the design of articles for medical journals.Results. The articles analyzed with the results of RCTs in journals met most of the necessary criteria. The authors paid the least attention to such details of the methodology when publishing a description of the sample calculation (2 out of 5 publications), the type of randomization (2 out of 5 publications), the mechanism of blinding participants (3 out of 5 publications), and implementation and masking (1 out of 5 publications). The inaccessibility of this information may have distorted the reader’s perception and trust in the results.Conclusion. The results show that the reviewed Russian medical journals declare requirements and recommendations for the publication of articles in accordance with the CONSORT standards. To increase readers' confidence in the practical and scientific significance of RCTs, it is necessary to consider the CONSORT requirements and strive to follow them.